Analisis Perhitungan Overall Equipment Effectiveness dan Diagram Fishbone pada Mesin Slitter di PT XZ - Lubis, Dinda Putri; Sumarjo, Jojo; Hanifi, Rizal (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research discusses the analysis of Overall Equipment Effectiveness (OEE) calculations on slitter machines at PT. XZ which focuses on increasing production efficiency and effectiveness. As market demand for high quality and productivity increases, it is important to evaluate machine performance to identify areas for improvement. The aim of this research is to understand how OEE can be used to assess the effectiveness of slitter machines and the factors that influence their performance. The methods used in this research include direct observation, collecting machine performance data, and analysis using the OEE formula which includes availability, performance and quality. The analysis results show that the average OEE of the slitter machine is 90.36%, which shows that the machine is operating at a good level of efficiency. However, there are several inhibiting factors identified through the fishbone diagram, such as unexpected machine breakdowns, delays in material delivery, and lack of operator training. The main conclusion of this study emphasizes the need for proper maintenance and operator awareness in maintaining heavy equipment to increase overall effectiveness and productivity. Keywords: Fishbone Diagram, Machine Performance, Overall Equipment Effectiveness, Production Efficiency, Slitter Machines